Requirements for open water and irrigation system SCADA software - Clout, Peter, author; Laughlin, Cathy, author; Steinman, David, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
A successful modern SCADA system will generally require some form of software to drive communications, control processing, and store data. This must not only operate as required on the first day of operation, but it has to be easily modified by the users to reflect changes that occur every day. These changes include expansion of the system as well as calibration changes and other SCADA changes to reflect changes in the network and variable field conditions. There are a multitude of SCADA software packages that exist today, generally developed for manufacturing, utility, or scientific applications. However, irrigation canals have some unusual and unique requirements which must be met. Any successful implementation of a SCADA system must address those specific considerations. We list and discuss these requirements and detail the adaptation of a standard SCADA system, Vsystem.
SCADA and related technologies
SCADA software
Not digitized by CSUL Digital Services.
Presented at SCADA and related technologies for irrigation district modernization, II: a USCID water management conference held on June 6-9, 2007 in Denver, Colorado.